Cost of Fund (COF) and Operating Expenses on Operating Income (BOPO) on Profitability in PT Bank Rakyat Indonesia (Persero) Tbk from 2012 to 2021 - Ardy Sofyan (Indonesian Financial Review, 2022)
This study aims to determine the effect of COF and BOPO on ROA at PT Bank Rakyat Indonesia (Persero) Tbk. This research method uses a quantitative descriptive design. The sample selection was done by purposive sampling method. The population used in this study was a financial summary report and equity participation in PT Bank Rakyat Indonesia (Persero) Tbk. The sample used is the company's financial statements for 2012-2021. The data method used in this research is multiple linear regression analysis, classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The result shows that there is autocorrelation in multiple regression model so the autoregressive (1) is used to fix the problem. The new model shows that BOPO has negative effect significantly effect on ROA partially, contrast to COF has not significant on ROA. ROA are significantly affected by COF and BOPO with AR(1) model.